Brain Molecular Aging, Promotion of Neurological Disease and Modulation by Sirtuin5 Longevity Gene Polymorphism - Glorioso, Christin (2010)
Mechanisms determining characteristic age of onset for neurological diseases are largely unknown. Normal brain aging associates with robust and progressive transcriptome changes (“molecular aging”), but the intersection with disease pathways is mostly uncharacterized. Here, using cross-cohort microarray analysis of four human brain areas, we show that neurological disease pathways largely overlap with molecular aging and that subjects carrying a newly-characterized low-expressing polymorphism in a putative longevity gene (Sirtuin5; SIRT5(prom2)) have older brain molecular ages. Specifically, molecular aging was remarkably conserved across cohorts and brain areas, and included numerous developmental and transcription-regulator genes. Neurological disease-associated genes were highly overrepresented within age-related genes and changed almost unanimously in pro-disease directions, together suggesting an underlying genetic “program” of aging that progressively promotes disease. To begin testing this putative pathway, we developed and used an age-biosignature to assess five candidate longevity gene polymorphisms association with molecular aging rates. Most robustly, aging was accelerated in cingulate, but not amygdala, of subjects carrying a SIRT5 promoter polymorphism (+9yrs, p=0.004), in concordance with cingulate-specific decreased SIRT5 expression. This effect was driven by a set of core transcripts (+24 yrs, p=0.0004), many of which were mitochondrial, including Parkinson’s disease genes, PINK1 and DJ1/PARK7, hence suggesting that SIRT5(prom2) may represent a risk factor for mitochondrial dysfunction-related diseases, including Parkinson s, through accelerated molecular aging of disease-related genes. Based on these results we speculate that a “common mechanism” may underlie age of onset across several neurological diseases. Confirming this pathway and its regulation by common genetic variants would provide new strategies for predicting, delaying, and treating neurological diseases.